Study of the relation between kVp and X-ray tube output of general X-ray machine at Hua Hin Hospital, Prachuap Khiri Khan - Bunkloy, Chawee (Journal of Associated Medical Sciences, 2017)
Introduction: X-rays are used to diagnose abnormalities in body. However, during radiographs patients will receive radiation doses. As X-ray machine has different quantities and quality of X-rays, it is therefore important for radiological technologists to set radiation doses for particular patients. Objectives: To study the X-ray tube output for general x-ray equipment and to evaluate radiation dose of patient at Hua Hin Hospital, Prachuap Khiri khan. Materials and methods: Relationship between kVp and X-ray tube output of the X-ray machine (Shimadzu HD150B-30 SN: 6114462, Philips Duo Diagnost SN: 04612 and Carestream DRX Revolution SN: 0722) was studied. Entrance surface air kerma of patients exposed from general X-ray machine was evaluated according to the guidelines of IAEA TRS No. 457. Results: Regression of output from Shimadzu HD150B-30, Philips Duo Diagnost output, and Carestream DRX Revolution was 0.003707 x kVp-0.137668, 0.003598 x kVp-0.134144, and 0.003712 x kVp -0.136235, respectively. ESAKs of Skull AP 1.37, 1.32, 1.18 and lateral 0.86, 0.83, 0.90 mGy, chest PA 0.13, 0.12, 0.06 and lateral 0.80, 0.77, 0.64 mGy, T spine AP 1.85, 1.83, 1.33 and lateral 8.80, 8.52, 7.22 mGy, abdomen AP 1.94, 1.88, 1.37 mGy, LS spine AP 2.16, 2.14, 1.55 and lateral 10.99, 10.64, 8.32 mGy, pelvis AP 1.55, 1.50, 0.96 mGy and hip AP 1.32, 1.28, 0.75 mGy were observed from Shimadzu HD150B-30, Philips Duo Diagnost and Carestream DRX Revolution, respectively. Conclusion: ESAKs of this study were lower than dose reference levels of IAEA.